Epigenetic regulation of TIMP1 expression by 8‐oxoguanine DNA glycosylase‐1 binding to DNA:RNA hybrid. Issue 12 (25th October 2019) - Pan, Lang; Wang, Hui; Luo, Jinhua; Zeng, Ji; Pi, Jiao; Liu, Huijun; Liu, Chi; Ba, Xueqing; Qu, Xiangping; Xiang, Yang; Boldogh, Istvan; Qin, Xiaoqun
Abstract : 8‐Oxoguanine DNA glycosylase‐1 (OGG1)‐initiated base excision repair pathway is primarily responsible for 7, 8‐dihydro‐8‐oxoguanine (8‐oxoG) removal from DNA. Recent studies, however, have shown that 8‐oxoG in gene regulatory elements may serve as an epigenetic mark, and OGG1 has distinct functions in modulating gene expression. Genome‐wide mapping of oxidative stress‐induced OGG1 enrichment within introns was documented, but its significance has not yet been fully characterized. Here, we explored whether OGG1 recruited to intron 1 of tissue inhibitor of metalloproteinase‐1 (TIMP1) gene and modulated its expression. Using chromatin and DNA:RNA hybrid immunoprecipitation assays, we report recruitment of OGG1 to the DNA:RNA hybrid in intron 1, where it increases nascent RNA but lowers mRNA levels in O3 ‐exposed human airway epithelial cells and mouse lungs. Decrease in TIMP1 expression is alleviated by antioxidant administration, small interfering RNA depletion, or inhibition of OGG1 binding to its genomic substrate. In vitro studies revealed direct interaction between OGG1 and 8‐oxoG containing DNA:RNA hybrid, without excision of its substrate. Inhibition of OGG1 binding to DNA:RNA hybrid translated into an increase in TIMP1 expression and a decrease in oxidant‐induced lung inflammatory responses as well as airway remodeling. Data documented here reveal a novel molecular link between OGG1 at damaged sites and transcription dynamics that may contribute to oxidative stress‐induced cellular and tissue responses.—Pan, L., Wang, H., Luo, J., Zeng J., Pi, J., Liu, H., Liu, C., Ba, X., Qu, X., Xiang Y., Boldogh, I., Qin, X. Epigenetic regulation of TIMP1 expression by 8‐oxoguanine DNA glycosylase‐1 binding to DNA:RNA hybrid. FASEB J. 33, 14159‐14170 (2019). www.fasebj.org